Accountability of the Use of Village Funds in Physical Development in the Lamokato Village Area - Restina Maulyanti; La Ode Asrun Azis R; Fetni (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze and describe the accountability of village fund usage in physical development in Lamokato Village. This study uses a qualitative approach with a descriptive research type, which aims to analyze or describe the accountability of village fund usage in physical development. The research location is in Lamokato Village, Kolaka District, Kolaka Regency. Data collection was carried out through observation and in-depth interviews with village officials and related parties. The allocation of village funds during the research period showed an increase and policy adjustment, namely IDR 795,614,000 in 2023, IDR 809,541,800 in 2024, and IDR 808,447,000 in 2025, which after the efficiency policy became IDR 775,198,000, with an additional budget of IDR 100,000,000 specifically allocated for drainage construction through the support of Bappeda. The results of the study show that legal accountability and honesty have been well implemented through compliance with administrative procedures, the preparation of comprehensive accountability reports, and the absence of legal violations. Managerial accountability is also functioning well, as evidenced by the preparation of structured planning documents such as the RKA and RAB, as well as the existence of a tiered monitoring mechanism. Program accountability shows that physical development has been tailored to community needs through development planning deliberations, although its effectiveness has not been felt evenly. Policy and financial accountability have basically been implemented in accordance with regulations, but still face obstacles in the form of budget constraints, low participation by some residents, and uneven transparency of information to the community. Therefore, it is necessary to strengthen community participation, public communication, and information disclosure in order to achieve more comprehensive accountability